Coupled computational fluid dynamics-population balance model approach for investigating effect of breakage, coalescence, and interfacial forces in continuous emulsification using static mixers - Salunkhe, Neha Sudhakar; Dastane, Gaurav; Mali, Chaitanya R. (Industrial & Engineering Chemistry Research, 2026)
This study employs a coupled CFD-PBM framework to investigate the effects of breakage and coalescence kernels as well as interfacial force models on droplet dynamics in turbulent liquid-liquid dispersions. An Euler-Euler two-phase model integrated with the population balance model was used to evaluate the influence of turbulence models and breakup-coalescence kernels on droplet formation. The role of interfacial forces, including drag, lift, and turbulent dispersion, was systematically assessed with respect to interfacial area concentration, dispersed phase volume fraction variation, turbulent dissipation rate, Sauter mean diameter (d 32), and droplet size distribution. Through sensitivity analysis, an optimized CFD-PBM model was developed, capable of accurately predicting droplet dynamics. The predicted d 32 showed excellent agreement with the measured experimental data, with a deviation of approximately 0.2% relative to the reported values. Incorporating the lift force improved the prediction of dispersed phase volume fraction by approximately 6.06%, while the inclusion of the turbulent dispersion force enhanced the phase redistribution and increased the local turbulent dissipation rate in the initial mixing zone by nearly 4.68%, thereby promoting droplet breakage. Furthermore, spectral analysis of velocity time-series data using the fast Fourier transform revealed a -5/3 slope in the energy spectrum, confirming that the simulations captured the inertial subrange of turbulence.

Selection of tubular reactor configurations for a confined space: analysis of space-fillingness and performance - Mali, Chaitanya R.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2026)
Introducing bends or coiling in a tubular reactor promotes Dean vortices, which enhance radial mixing as well as heat and mass transfer. Exploring compact geometries that strengthen curvature-induced mixing is highly beneficial for continuous flow synthesis across scales. Despite their advantages, selecting an appropriate configuration of tubular reactors in a given space (jacket) requires careful evaluation of multiple factors, including energy efficiency, dispersion behavior, heat transfer performance, and spatial compactness. This paper presents a holistic framework for selecting an optimal configuration of a tubular reactor within a confinement (jacket) based on energy efficiency, dispersion behavior, heat transfer, and spatial compactness. Ten distinct configurations are explored based on geometrical characterization and single-phase Computational Fluid Dynamics (CFD) simulations. Each configuration is evaluated for flow patterns, pressure drop, residence time distribution (RTD), and jacket-side flow distribution. The results demonstrate that geometric design, especially the number and arrangement of bends, has a pronounced impact on reactor performance, influencing both compactness and dispersion characteristics. A combined qualitative-quantitative assessment is employed, utilizing radar plots (which capture key simulation and geometric data) and a K-means clustering unsupervised learning algorithm, along with a derived performance index (Pi), to rank configurations based on their geometric attributes. This approach forms a robust basis for selection and design guidance. The study indicates that while individual designs offer specific advantages, coil geometries such as multihelix, spiral, and elongated spirals deliver optimal overall performance.